INFORMATION LITERACY ASSESSMENT: MOVING BEYOND COMPUTER LITERACY. - Higntte, Michael; Margavio, Thomas M.; Margavio, Geanie W. (College Student Journal, 2009)
Information literacy is a concept that has evolved as a result of recent efforts to move technology-based instruction and research to a level above the long-held concepts previously associated with "computer literacy"; the focus of information literacy education being the development of students' abilities to construct/collect and analyze information in a way that provides the basis for effective decision making. In this study, the authors assess the information literacy levels of some 600 college students with results of the study indicating that students' information literacy achievement levels were modest at best — only 40% of the students achieved a "passing" grade on the exam. Additional results show significant differences in achievement among the various groups of students with, for example, females scoring significantly higher than males on the exam.